Generations, Inc from boomers to linksters--managing the friction between generations at work - Johnson, Meagan 1970-; Johnson, Larry 1947- (AMACOM, 2010)
When Woodstock meets Facebook at the watercooler.
Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Diversity in the workplace -- Management; Intergenerational relations; Intergenerational communication; Conflict of generations; Personnel management; Multiculturalisme en milieu de travail; Gestion; Relations entre générations; Communication entre générations; Conflit de générations; Personnel; Direction; BUSINESS & ECONOMICS; Workplace Culture; BUSINESS & ECONOMICS; Human Resources & Personnel Management; Diversity in the workplace; Management; dissertations; Academic theses; Thèses et écrits académiques